Remodelamento da matriz extracelular e respostas cardíacas funcionais em ratos idosos submetidos a treinamento resistido - Guzzoni, Vinicius (Universidade Federal de São Carlos, 2016)
INTRODUCTION: It is well documented that aging causes morphological and functional alterations in the heart. Cardiac ECM remodeling is one event of structural changes in left ventricle (LV), which is modulated by MMPs/TIMPs balance and may lead to cardiac fibrosis. To prevent such effects inherent of aging, aerobic exercise training has been suggested to improve the cardiac fibrosis and function. However the effects of resistance training (RT) remains unclear. Whether that RT could alter cardiac function following cardiac ECM remodeling is uncertain. PURPOSE: to investigate the chronic effects of high intensity resistance training (RT) in the extracellular matrix (ECM) remodeling of left ventricle (LV) and cardiac function in old rats. PROCEDURES: Rats with 3 and 21 months-age were assigned as young sedentary (YS), young trained (YT), old sedentary (OS) and old trained (OT). The trained groups (YT and OT) were submitted to high-intensity RT protocol (3 times a week during 12 weeks). After 48h post-training, hemodynamic and intra-ventricular pressures were recorded. LV myocyte width, LV connective tissue and collagen fibrils were analyzed. MMP-2 activity, gene and protein expression from ECM components as well as angiotensin II (Ang-II) and atrial natriuretic peptide (ANP) were evaluated FINDINGS: LV myocyte width and connective tissue were reduced in OT rats. RT increased the MMP-2 activity in OT rats and improved the agerelated increase in the left ventricle end diastolic pressure (LVEDP). The RT unchanged Ang-II and ANP in LV of old rats. CONCLUSION: RT was effective to decrease LV connective tissue, which was associated with increased ECM remodeling by MMP-2 activity in LV tissue and improvement of LVEDP in aging rats. Our results point out the importance of RT in ECM homeostasis and diastolic function in experimental aging model.
Effects of high-intensity resistance training in the extracellular matrix (ECM) and diastolic function in left ventricle of old male rats.
Keywords: Envelhecimento; Treinamento Resistido; Ventrículo Esquerdo; Matriz Extracelular; Função Diastólica; Aging; Resistance Training; Left Ventricle; Extracellular Matrix; Diastolic Function; CIENCIAS BIOLOGICAS